Assessment of the Biomechanical Effects of Hindfoot Alignment in Supination External Rotation Malleolar Fractures in a Cadaveric Model - Angela Seidel MD, MBA; Amal Chidda MD; Virginie Perez MD; Fabian Krause MD; Ivan Zderic MS; Boyko Gueorguiev PhD; Karl-Andre Lalonde MD; Brad Meulenkamp MD (Foot & Ankle Orthopaedics)
Category: Trauma; Hindfoot Introduction/Purpose: Pressure distribution in the ankle joint is known to be dependent on various factors, including hindfoot alignment. We seek to evaluate how hindfoot alignment affects contact pressures in the ankle joint in the setting of supination external rotation (SER) type ankle fractures. Methods: SER fractures were created in 10 human cadaver lower extremity specimens, simulating progressive stages of injury: without fracture (step 0), SER fracture and intact deltoid ligament (step1), superficial deltoid ligament disruption (step2) and deep deltoid ligament disruption (step3). At each step, varus and valgus alignment was simulated by displacing the calcaneal tuberosity 7mm medial or lateral. Each limb was axially loaded following each osteotomy at a static load of 350N. The center of force (COF), contact area (CA), and peak contact pressure (PP) under load were measured, and x-rays of the ankle mortise were taken to analyze the medial clear space (MCS) and talar tilt (TT). Results: The COF (5.3mm, p=0.030) and the CA (-188.4 mm 2 , p=0.015) changed in step 3 in the valgus hindfoot alignment compared to baseline parameters, indicating the importance of deep deltoid ligament integrity in maintaining normal ankle joint contact stress in the valgus hindfoot. These changes were not seen in the setting of varus alignment (COF: 2,3mm, p=0.059; CA -121mm 2 , p=0.133). PP were found to not change significantly in either varus or valgus (varus:-4.9N, p=0.132;valgus:-4N, p =0.464). The MCS demonstrated widening in step 3 compared to step 2 (0.7mm, p=0.020) in both varus and valgus hindfoot. The TT increased significantly in step 3 in the valgus hindfoot (2.8°, p=0.020) compared to step 0. Conclusion: SERIV fractures with valgus hindfoot alignment showed significant changes in pressure distribution and radiographic parameters when compared to SER IV fractures with varus hindfoot alignment. Based on this cadaver modelling study, patients with SERIV fracture with varus hindfoot alignment and complete deltoid ligament lesion may not need fracture fixation, whereas those with valgus hindfoot alignment likely need fracture fixation. Results of the measurements of COF (center of force), CA (contact area), PP (peak contact pressure) MCS (medical clear space) in mm, TT (talar tilt) in degree in varus and valgus hindfoot alignment in the different steps. It shows the mean and (standard deviation)